(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we investigate that the spacer layer thickness affects the polarization effect on thetwo-dimensional electron gas (2DEG) concentration and current-voltage properties in an MgZnO/ZnO hetero structure. In the conduction band edge profile, MgZnO/ZnO hetero structure with athick layer of spacer shows sharper bending. As a result, the MgZnO/ZnO hetero structure witha relatively thick layer of spacer is expected to surpass the MgZnO/ZnO hetero structure with athin layer of spacer in the carrier confinement. However, if the spacer layer thickness exceeds 30nm, the carrier concentration will no longer increase. The drain current and pinch-off voltage havebeen shown to be proportional to the spacer layer thickness from the addition in electron densitydue to the increased spacer layer thickness.